Caracterização molecular de cepas clinicas de Sporothrix spp isoladas da Paraíba e potencial antifúngico do (-) mirtenol como alternativa terapêutica - Silva, Larissa Alves da (2024)
Sporotrichosis is a subcutaneous mycosis, with a subacute or current course, capable of affecting both humans and animals. This infection is caused by a fungus belonging to the genus Sporothrix, with a cosmopolitan geographic distribution. According to the epidemiological bulletin from the health department of the state of Paraíba, the number of reported cases of the disease has increased in recent years, so it is necessary to investigate the population distribution of the isolated species in the state. Furthermore, the increase in antifungal resistance, the cost of treatment with current antifungals and their limited available arsenal, has driven the search for new substances with antifungal activity, and medicinal plants and their phytoconstituents have been widely investigated. In view of this, the objective of this study was to analyze the genetic diversity, the distribution of mating type and evaluate the antifungal activity of (-) - myrtenol in clinical isolates of human sporotrichosis in Paraíba-Brazil. For this, a total of 36 cultures of Sporothrix spp., from confirmed cases of sporotrichosis, previously isolated from patients treated at the Lauro Wanderley University Hospital were used and their clinical and demographic data were found. Species identification was carried out using the species-specific PCR technique with markers directed to the calmodulin gene. The mating type idiomorph of the species was identified by PCR using primers rotating at the MAT1-1 and MAT1-2 loci. AFLP were used for genotyping the isolates. To analyze the antifungal activity of (-) – myrtenol against the species tested, the Minimum Inhibitory Concentration (MIC) was determined; Minimum Fungicide Concentration (CFM), the formation of biofilm and the action of this monoterpene on the biofilm in the adhesion and mature phase, in addition to evaluating the cytotoxicity of (-) – myrtenol in human keratinocyte cells (HaCaT). As a result, the distribution of the disease shows that cases occurred in the capital of João Pessoa and the metropolitan region. Among the 36 Sporothrix isolates, 75% affected females, with 69% occurring in the lymphocutaneous form, and 98% of transmission was via the zoonotic route. All isolates were identified by molecular methods as S. brasiliensis and detected the presence of a single sexual idiomorph, MAT1-2, probably that this species originates from the genotypes of species from Rio de Janeiro. The AFLP results indicate the possibility of the circulation of one or two genetic groups in João Pessoa and the metropolitan region. (-) - myrtenol showed strong antifungal activity against all strains of S. brasiliensis tested, with 84% of the strains tested with MIC at 128 µg/mL and CFM at 256 µg/mL, exhibiting fungicidal action, it was also able to reduce significantly inhibit biofilm formation and inhibit mature biofilm. Regarding cytotoxicity, the monoterpene did not significantly reduce cell viability at MIC (128 µg/mL). Given the results presented, our data genetically characterized isolates from Paraíba for the first time, observing low intragenotypic variation. The findings of this research suggest that (-)-myrtenol represents a new and promising therapeutic alternative in the treatment of fungal infections caused by Sporothrix spp.